(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Biochemical, microbial and sensory qualities of burger patty and fish mince prepared from Mozambique tilapia were determined during frozen storage condition (-18 ºC) up to 75 days. Significant decrease (P>0.05) in moisture and lipid contents of mince and burger were observed during the storage period although moisture and lipid contents of burger was higher than the mince. Protein content of mince and burger reduced at the end of storage period however, reduction rate was not significant (p>0.05) and protein content of burger was slightly higher than that of mince. Ash content of both mince and burger increased significantly (p<0.05) throughout the storage period and ash content in burger was higher than that of mince. TVB-N content in fish mince and burger increased significantly (p<0.05). The pH value increased in both groups but the rate of increment was not significant (p>0.05). Microbial load of burger was found higher than mince but microbial load of both groups remained under maximum allowable count until the end of the storage period. Sensory parameters (color, texture, taste and overall acceptability) of burger decreased significantly (p<0.05), whereas, all parameters other than texture remained in good condition until the end of the storage period. J Bangladesh Agril Univ 18(2): 524–528, 2020 https://doi.org/10.5455/JBAU.86202